The mediation of the cultures of the peoples of the Cordillera in radio broadcasting in Baguio City (1959-2010) - Telles, Jason Paolo R. 1988-
"Using postcolonial theory, specifically the concept of appropriation, and the political economy of media as frameworks, this research provides a history of how the practice of radio broadcasting in Baguio City has been used by local radio practitioners in expressing the cultures of the people of the Cordillera. Through interviews with key informants and archival research, it has been found that since the establishment of the first radio stations in Baguio until the 2000s, there have been continuous efforts in expressing the cultures of the people of the Cordillera in the local radio operations and content. The methods that were used for cultural expression were the airing of locally-produced songs, the incorporation of the Cordillera - its locations, events, stories, ways of living, ad practices, among others-in program content and titles, use of local languages in the Cordillera, interviewing and featuring of peoples of the Cordillera, hiring of Cordillera locals, and blocktiming. Meanwhile, the motivations for the expression of such cultures in Baguio radio were cultural, economic, political, technological, and religious in character. Ultimately, airtime in radio has become a space for the expression of the people of the Cordillera's cultures that have been "bothered" since the Philippine colonial times."